Developing the Tissue Engineered Heart Valve - a Descriptive Hemodynamic and Ultrasound in Vitro Characterization Study of Heart Valves in a Bioreactor - Ionela MOVILEANU; Dan Octavian NISTOR; Leslie SIERAD; Klara BRINZANIUC; Codrut OPRITA; Marius Mihai HARPA; Terezia PREDA; Ovidiu COTOI; Hussam AL HUSSEIN; Hamida AL HUSSEIN; Alexandru CHERTES; Horatiu SUCIU; et al. (Sciendo, 2021)
The inherent limitations of current heart valve substitutes create the premise for the Tissue Engineered Heart Valve (TEHV), considered the perfect substitute. We aimed to compare in vitro hemodynamic performances of our TEHV, the conventional prosthetic valve and similar porcine valves, by ultrasonography and geometry resulting in six valve models analysis. In a bioreactor, pulmonary and aortic physiology were replicated thus hemodynamic characteristics were tested. Using ultrasound, transvalvular pressure gradients and flow were measured and used to calculate their valvular functional area (VFA) and using a high-speed camera, the geometric peak opening area (GOA) was assessed. The obtained results were normalized to the diameter of the biological prosthesis in order to increase the measurement's accuracy. The ultrasound revealed normal function of all valves and physiologic transvalvular pressure gradients. The TEHV scaffold revealed absence of laceration or dehiscence, and performances in accordance with the control prostheses. The GOA was facile to obtain and the normalized values proved to be greater than the calculated functional area in all analyzed cases and the peak opening areas resulted lesser for the aortic conditions for all six used valves prototypes. To our knowledge, this is the first study to use bioreactors, for in vitro evaluation of heart valves.